PELATIHAN PEMBUKUAN SEDERHANA PELAKU USAHA KECIL DI DUSUN KERANJANG DESA WAYAME - Troice Else Siahaya; Fredy Hendry Louhenapessy; Angelia Tomasoa (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Small business actors in Keranjang Hamlet, Wayame Village, Teluk Ambon Sub-district face several fundamental challenges, including limited awareness of the importance of bookkeeping, the absence of separation between personal and business finances, and insufficient skills in preparing simple financial reports. This Community Service Program aims to enhance the understanding and practical skills of small business actors in recording financial transactions in an orderly and systematic manner, so that business income, expenses, and profits can be accurately monitored and measured. The program involved 15 participants comprising farming families and youth groups, implemented through three stages: counseling, learning by doing training, and direct mentoring. The results demonstrated a significant improvement in participants' understanding and skills, with all participants reporting that the training materials were easy to comprehend and immediately applicable to their daily business activities. This program is expected to serve as a replicable model for empowering small business actors through financial literacy initiatives across other areas of Maluku.